Patterns of resistance to values education a thematic analysis - Abuso, Julian E. (Education quarterly.)
This paper identifies some existing patterns of resistance to values education in Philippine society and in the education sector. Secondly, this presentation examines critically values education in the context of what goes on in the identified sectors. As this paper is addressed to a crowd of social anthropologist rather than to a corp of elementary and secondary teachers, some background information on values education is in order.